2008
DOI: 10.1016/j.amepre.2007.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Diabetes Risk in American Indian Women

Abstract: A culturally influenced, low-intensity lifestyle intervention can improve self-reported intakes of vegetables and fruit over 18 months in young, urban American Indian women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 47 publications
1
43
0
Order By: Relevance
“…Of the 51 included studies (18 480 participants), 44 were RCTs28–70 and seven were cluster RCTs71–77 conducted in Europe (n=25), the USA (n=18), Australia (n=7) and China (n=1). The majority of studies were carried out in a mixed gender population (n=35); 13 studies targeted women only29 42 50 51 56 57 60 61 67 69 71 76 and three studies targeted men only 29 31 44. Most studies included participants aged between 18–60 years (n=44), while seven studies included participants older than 60 years of age 33 35 37 38 48 62 72.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 51 included studies (18 480 participants), 44 were RCTs28–70 and seven were cluster RCTs71–77 conducted in Europe (n=25), the USA (n=18), Australia (n=7) and China (n=1). The majority of studies were carried out in a mixed gender population (n=35); 13 studies targeted women only29 42 50 51 56 57 60 61 67 69 71 76 and three studies targeted men only 29 31 44. Most studies included participants aged between 18–60 years (n=44), while seven studies included participants older than 60 years of age 33 35 37 38 48 62 72.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies employed an intervention specifically to reduce SB,40 44 63 16 studies aimed at increasing PA levels,30 35 36 39 41 46 48 49 55 58–60 64 66 72 78 nine studies combined both approaches of reducing SB and increasing PA levels,32 43 53 62 65 68 70 76 77 one study assessed the effect of a dietary intervention on SB,61 and 22 studies (20 reports) applied a multicomponent lifestyle intervention and observed effects on sedentary behaviour (among other outcomes) 29 33 34 37 38 42 45 47 50–52 54 56 57 67 69 71 73 74 75. Twenty studies offered an alternative intervention,30 36 39–41 45 46 49 52–55 59 61–63 68 72 77 10 studies the usual/routine care,29 37 38 42 50 51 67 71 74 75 seven studies used a waiting list control,29 34 48 64 69 76 78 five studies an attention control,35 44 56 57 60 and control participants of seven studies received no intervention at all 32 33 43 47 58 66 …”
Section: Resultsmentioning
confidence: 99%
“…However, many Indigenous communities operate as autonomous entities in keeping with a philosophy of self-determination as opposed to the imposition of colonial rule and lack of autonomy. We found no evidence of formal (Tobe et al, 2006) Canada First Nations Hypertensive treatment in diabetics RCT (Simmons et al, 2000) New Zealand Maori and Pacific Islanders Medication packaging-blister packs RCT (Grossi et al, 1997) United States Native Americans (Pima heritage) Treatment of periodontal disease on HBA1C RCT (Mayer-Davis et al, 2004) United States American Indians Dietary and lifestyle modification B RCT (Fleg et al, 2008) United States American Indians Lowering blood pressure and cholesterol in diabetics B RCT United States American Indians Lowering blood pressure and cholesterol in diabetics RCT (Thompson et al, 2008) United States American Indian women Dietary and lifestyle modification CBA (Daniel et al, 1999) Canada Aboriginal Canadians Dietary and lifestyle modification CBA (Heath et al, 1991) United States Zuni Indians Dietary and lifestyle modification C CBA (Paradis et al, 2005) Canada Mohawk children (Kahnawake) Dietary and lifestyle modification CBA (Robertson et al, 2007) United States American Indians (Northern Plains) Diabetes management-interactive website CBA (Wilson et al, 2005) United States American Indians/Alaska natives Nurse case managers CBA (Gilliland et al, 2002) United States Native Americans (New Mexico) Dietary and lifestyle modification CBA (self selected control) (Beckham et al, 2008) United States Native Hawaiian/Samoan Diabetes management-community health workers CBA (historical control) (Gray-Donald et al, 2000) Canada Cree (James Bay, Quebec) Gestational diabetes-dietary and lifestyle modification C CBA (historical control) (Jimenez et al, 2003) Canada Mohawk children (Kahnawake) Dietary education D ITS (1 base, 2 post) (Ritenbaugh et al, 2003) United States Zuni Indian youth Dietary and lifestyle modification ITS (1 base, 2 post) (Shand et al, 2007) New Zealand Maori-Polynesian Efficacy of treatment (Pioglitazone) ITS (1 base, 2 post) and CBA (self selected controls) (Rowley et al, 2000) Australia…”
Section: Discussionmentioning
confidence: 97%
“…However, 'protection against contamination', which entails ensuring that controls are not exposed to the intervention, was lacking in two studies as the treatment in one study was being given to both arms by the same physician, therefore risking a possible halo effect in prescribing patterns (Tobe et al, 2006). In the other study, individuals were randomized within a community-based setting rather than larger clusters, which meant that there was a high likelihood that knowledge presented in the intervention was shared with control participants (Thompson et al, 2008). Three-quarters (n = 21) of the intervention studies relating to Type 2 and gestational diabetes in Indigenous populations did not fulfil EPOC requirements for contributing to the evidence base.…”
Section: Study Design Standards (Minimum Requirements For Inclusion Imentioning
confidence: 97%
“…Other studies showed that well-structured interventions had normalized fasting and 2-hour plasma glucose after 6 months [30], one year [31][32][33] [36]. Only a few studies, mostly those that had a short follow-up period, failed to show the benefits of well-structured exercise programs [37,38].…”
Section: Interventional Studiesmentioning
confidence: 97%